2018
DOI: 10.1117/1.jmi.5.1.013503
|View full text |Cite
|
Sign up to set email alerts
|

Dose and diagnostic performance comparison between phase-contrast mammography with synchrotron radiation and digital mammography: a clinical study report

Abstract: Two dosimetric quantities [mean glandular dose (MGD) and entrance surface air kerma (ESAK)] and the diagnostic performance of phase-contrast mammography with synchrotron radiation (MSR) are compared to conventional digital mammography (DM). Seventy-one patients (age range, 41 to 82 years) underwent MSR after a DM examination if questionable or suspicious breast abnormalities were not clarified by ultrasonography. The MGD and the ESAK delivered in both examinations were evaluated and compared. Two on-site radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 50 publications
(75 reference statements)
1
13
0
Order By: Relevance
“…In this framework, the first x-ray PhC mammographic clinical study performed with SR, involving more than 70 patients, has demonstrated an improvement in the image quality and diagnostic performance when compared with the conventional state-of-the-art mammography. [7][8][9] The transition of PhC mammography from synchrotron to hospitals is a research topic for several groups. [10][11][12][13][14][15] At the same time, the advent of more efficient digital detectors and powerful reconstruction algorithms allowed the realization of three-dimensional (3-D) mammographic systems, such as tomosynthesis and tomographic scanners.…”
Section: Introductionmentioning
confidence: 99%
“…In this framework, the first x-ray PhC mammographic clinical study performed with SR, involving more than 70 patients, has demonstrated an improvement in the image quality and diagnostic performance when compared with the conventional state-of-the-art mammography. [7][8][9] The transition of PhC mammography from synchrotron to hospitals is a research topic for several groups. [10][11][12][13][14][15] At the same time, the advent of more efficient digital detectors and powerful reconstruction algorithms allowed the realization of three-dimensional (3-D) mammographic systems, such as tomosynthesis and tomographic scanners.…”
Section: Introductionmentioning
confidence: 99%
“…3c) are in good agreement with Fedon et al . 29 . The difference in skin layer models between Dance and Wu also leads to slightly higher AGD for thin breasts with the Dance model 29 .…”
Section: Discussionmentioning
confidence: 99%
“…The SYRMA-3D collaboration was established to set up the first clinical trial of phase-contrast breast CT with synchrotron radiation (SR) at the Elettra synchrotron light source facility in Trieste, Italy, based on the previous clinical trial for SR mammography using phase-contrast techniques; that study highlighted an increase of image quality with respect to standard digital mammography (Castelli et al, 2011;Fedon et al, 2018;Longo et al, 2014). Breast imaging with SR may also be compatible with K-edge subtraction imaging with iodine contrast medium (Thomlinson et al, 2018) for enhanced visibility of tumor masses.…”
Section: Introductionmentioning
confidence: 99%